2014
DOI: 10.1002/app.41598
|View full text |Cite
|
Sign up to set email alerts
|

Flow characteristics of three enhanced oil recovery polymers in porous media

Abstract: This article presents an experimental study aiming to explore the relationship among rheological properties, flow characteristics in porous media, and enhanced oil recovery (EOR) performance of three typical EOR polymers. The results suggest that xanthan gum exhibits a very pronounced shear-thinning behavior, which is probably also the reason explaining its moderate adsorption extent within porous media (thickness of adsorbed layer, e 5 3.1 lm). The advanced viscoelastic properties coupled with the less adsorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 41 publications
(41 reference statements)
0
20
0
Order By: Relevance
“…The viscoelastic properties for polymer solutionsare used broadly to gain understanding into the molecular structure and deformation of polymers, and itplayed a crucial role in the oil recovery process. [42][43][44][45] Theoscillatory test were performed for both HPAM/silica hybrid and pure HPAM solutions, and the storage modulus (G'), loss modulus (G''), damping factor (tan δ) and complex viscosity (ƞ*) are plotted as a function of angular frequency ( ) in a high salinity solution (8 wt% NaCl) at 85 o C. The results showed that the solutions of both pure HPAM and HPAM/silica hybrids were elastically dominated (tan δ <1) over the investigated frequency range, and became more elastic as the NP concentration increased (Figure 11b). When the particle loading was increased from 0 wt% to 0.8 wt%, G' and G'' both increased (Figure 11a).…”
Section: Viscoelastic Propertiesat Differentnanoparticle Loadingsmentioning
confidence: 99%
“…The viscoelastic properties for polymer solutionsare used broadly to gain understanding into the molecular structure and deformation of polymers, and itplayed a crucial role in the oil recovery process. [42][43][44][45] Theoscillatory test were performed for both HPAM/silica hybrid and pure HPAM solutions, and the storage modulus (G'), loss modulus (G''), damping factor (tan δ) and complex viscosity (ƞ*) are plotted as a function of angular frequency ( ) in a high salinity solution (8 wt% NaCl) at 85 o C. The results showed that the solutions of both pure HPAM and HPAM/silica hybrids were elastically dominated (tan δ <1) over the investigated frequency range, and became more elastic as the NP concentration increased (Figure 11b). When the particle loading was increased from 0 wt% to 0.8 wt%, G' and G'' both increased (Figure 11a).…”
Section: Viscoelastic Propertiesat Differentnanoparticle Loadingsmentioning
confidence: 99%
“…The final oil recovery of the in-situ CO 2 foam reached up to 51.5 %. This phenomenon can be interpreted as: (1) In-situ generating CO 2 in the reservoir condition can displace the crude oil. (2) Reaction residues, alkali together with other chemical agents in the system, can reduce oil-water interfacial tension, and thus improve microscopic displacement efficiency.…”
Section: Sandpack Flooding Experimentsmentioning
confidence: 99%
“…The growth of global demand for energy, coupled with the high oil price, leads to the use of various techniques to stimulate oil production [1]. Bakhtiyarov et al [2] classified the techniques in three categories: finding new oil reservoirs, developing proven reservoirs, and improving the efficiency of oil production.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its unique structure, xanthan gum is quite resistant to mechanical shear and salinity. The chemical and physical properties of xanthan gum related to EOR use have been systematically investigated in our previous reports [58][59][60][61]. It was demonstrated that xanthan gum experienced less viscosity loss when exposed to harsh reservoir conditions compared with HPAM and hydrophobic polymers.…”
Section: Biopolymersmentioning
confidence: 99%